IMPACT OF INDIVIDUALIZED ALGEBRAIC BLOCKS STRATEGY ON STUDENTS ALGEBRA RETENTION: A CASE STUDY OF UPPER BASIC STUDENTS IN ABUJA MUNICIPAL AREA COUNCIL - OGBU N. A.; CHIBUIKE C., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
The study investigated the impact of individualized Algebraic blocks strategy on upper basic students’ retention in algebra. The population comprised 32,474 upper basic students in public upper basic schools in Abuja. Simple random sampling was used to select 158 students from two different schools. A quasi-experimental design was adopted for the study which was made up of one experimental group and a control group. Algebra Retention Test (ART) was the instrument used for data collection. The instrument was validated by two mathematics educators and one expert in measurement and evaluation for both face and content validation. Kuder Richardson’s formula KR-21 was used to estimate the reliability of the instrument and the index of ART was found to be 0.79. Mean and Standard deviation were used to answer research questions while Analysis of Covariance (ANCOVA) was used to test the hypotheses formulated at 0.05 level of significance. The study revealed that students taught algebra using individualized algebraic blocks strategy retained more than students taught using lecture method. Female students retained algebra concepts better than the male students in individualized algebraic blocks strategy. It was recommended among others, that teachers should adopt individualized algebraic blocks strategies in teaching algebra aspect of mathematics in upper basic schools to enhance students’ retention in mathematics.